Strawberry Leaf Extract Treatment Alleviates Cognitive Impairment by Activating Nrf2/HO-1 Signaling in Rats With Streptozotocin-Induced Diabetes - Zhang, Li; Ma, Qinghua; Zhou, Yanling (Frontiers in Aging Neuroscience, 2020)
Diabetes-associated cognitive impairment (DACI) is a common complication of diabetes mellitus (DM) that affects the central nervous system. Cognitive impairment, such as learning and memory impairment, and even dementia, is the main clinical manifestation of DACI. Unfortunately, there is no effective means by which to delay the cognitive symptoms of DM. Evidence has shown that strawberry leaf extract could alleviate cognitive decline, suppress oxidative stress and reduce inflammatory responses in rats. In the present study, we evaluated the effect of strawberry leaf extract on cognitive function in a rat model of the streptozotocin (STZ)-induced diabetes. After the continuous administration of strawberry leaf extract for four weeks, the Morris water maze (MWM) test results showed that the cognitive impairment of the rats was alleviated. Moreover, strawberry leaf extract significantly reduced the level of reactive oxygen species (ROS), decreased the level of malondialdehyde (MDA), improved the activity of superoxide dismutase (SOD) and catalase (CAT), decreased the mRNA expression of interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) and decreased the protein expression of caspase-3 and caspase-9 in the hippocampus of DM rats. In addition, transcription factor nuclear factor-erythroid 2 (NF-E2)-related factor 2 (Nrf2)/hemeoxygenase-1(HO-1) signalling was obviously activated by the administration of strawberry leaf extract. Our findings indicate that strawberry leaf extract may be a potential drug candidate for the treatment of DACI and may be used as a basis for further research on the development of drugs for cognitive impairment in diabetes.